Descartes. - Gombay, Andre (Blackwell great minds., 2007)
A bold and insightful departure from related texts, Descartes goes beyond the categorical associations placed on the philosophers ideas, and explores the subtleties of his beliefs.:.; An elegant, compelling and insightful introduction to Descartes' life and work.; Discusses a broad range of his most scrutinized philosophical thought, including his contributions to logic, philosophy of the mind, epistemology, metaphysics, the philosophy of science, and the philosophy of religion.; Explores the subtleties of Descartes' seemingly contradictory beliefs.; Addresses themes left unexamined in other.